Amplification and Description Techniques in the Translation of Arabic Phrases in Matan Al-Ghayah wa Al-Taqrib - Wiji Lestari; Yoyo Yoyo; Abdul Razif Zaini (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2020)
The translation from Arabic into Indonesian on the Islamic field has its long history. However, researches on the subject are a little bit rare. Therefore, the study of the item using a modern approach is required. This research described the use of amplification and descriptions techniques in the translation of Arabic phrases in the reading of Matan al-Ghayah wa al-Taqrib by Ahmad Ma'ruf Asrori. Besides, this paper aimed to describe the quality of the text that is seen from the aspect of readability. This research used a qualitative analysis combined with a quantitative data approach. The data were selected and classified based on procedures of translation techniques. The results showed that based on the amplification techniques there were 35 data in Matan al-Ghayah wa al-Taqrib found 35 which can be divided into four Arabic phrases based as follows: 1) 'atfy phrases are 12 data, 2) idhafy phrases are 13 data, 4) syibhu al-jumlah phrases are 5 data, and 5) adjective phrases are 5 data. Whereas in the description technique, the researchers found 31 data divided into five Arabic phrases based on their constituent elements, namely the 'atfy phrase 12 data, idhafy phrase 12 data, ‘adady phrase 3 data, syibhu al-jumlah phrase 3 data, and adjective phrase 2 data. From the translation quality, it showed that the use of these two techniques could be seen from the assessment of the readability aspects of 42 respondents. It rated 52% high readability on the amplification technique, and 56% high readability on the description technique. It means that the translator used more of these two techniques frequently rather than other techniques. It assumed that amplification and description techniques are much more applicable in the translation of Arabic books into Indonesian due to its acceptance of the cultural dimension of the targeted language.